Restaurants in the greater Athens area: a service for all? - Alex M. Deffner; Thomas Maloutas (European Regional Science Association (ERSA), 2002)
Eating (especially dining) in restaurants as a form of entertainment constitutes a practice that has been intensely developed, and socially broadened, in recent decades in most of the developed countries. The conditions in the labour market and the changing demographic structures have created much greater needs for consuming meals outside the home. At the same time, the growth of tourism, migration, and, more generally, of the international movement of people and goods have increased the relevant needs and have internationalized tastes. The percentage of the internationalization of a cuisine in a city is an indicator of its cosmopolitan character, something that is also connected to the level of local cuisine. The topic of the paper is the analysis of the spatial dimension of the growth of places for eating (excluding fast food restaurants and neighbourhood taverns) in the Greater Athens Area. The purpose of the paper is, using maps as a main tool, to uncover the geographical distribution of eating spaces (as part of cultural industries) in Greater Athens Area situating them in their urban, cultural, and economic context. This is analysed in connection with the impact of new phenomena such as the combination of shopping and eating and the building of multiplexes. The theoretical focus is on the consumption aspect in relation to the issue of tastes and dominant leisure tendencies, such as out-of-home and 'passive' activities. The main source used in this paper is a research carried out by the Institute of Urban and Rural Sociology of the NCSR and the Department of Planning and Regional Development of the University of Thessaly in the context of the Socio-economic Atlas of Greece. The main conclusions are: a) the dominance of the Greek cuisine (55% of the restaurants) co-exists with a large variety of categories of cuisine, b) the prices in restaurants can constitute a basis for certain hypotheses concerning the social differentiation of food provision as a service, since the cheaper places are the taverns and certain categories of national cuisine (Ethiopian, Egyptian, and Cypriot), while the most expensive ones are fusion and fish restaurants, as well as restaurants with the most established categories of national cuisine (Italian and French), c) there exist important internal differentiations in certain categories(in particular reference to pricing), d) the geography of categories shows a relatively equal geographical distribution of taverns combined with the concentration of the places of modern international cuisine and the most established categories of national cuisine in the areas where the higher social strata live or use to visit.
Keywords: 330